The Effects of Prostaglandin E2 Treatment on the Secretory Function of Mare Corpus Luteum Depends on the Site of Application: An in vivo Study - Piotrowska-Tomala, Katarzyna K.; Jonczyk, Agnieszka W.; Szóstek-Mioduchowska, Anna Z.; Żebrowska, Ewelina; Ferreira-Dias, Graca; Skarzynski, Dariusz J. (Frontiers in Veterinary Science, 2022)
We examined the effect of prostaglandin (PG) E2 on the secretory function of equine corpus luteum (CL), according to the application site: intra–CL injection versus an intrauterine (intra–U) administration. Moreover, the effect of intra–CL injection vs intra-U administration of both luteotropic factors: PGE2 and human chorionic gonadotropin (hCG) as a positive control, on CL function was additionally compared. Mares were assigned to the groups (n = 6/ per group): (i) an intra–CL saline injection (control); (ii) an intra–CL injection of PGE2 (5 mg/ml); (iii) an intra–CL injection of hCG (1,500 IU/ml); (iv) an intra–U saline administration (control); (v) an intra–U administration of PGE2 (5mg/5ml), and (vi) an intra–U administration of hCG (1,500 IU/5ml). Progesterone (P4) and PGE2 concentrations were measured in blood plasma samples collected at -2, -1, 0 (pre-treatment), and at 1, 2, 3, 4, 6, 8, 10, 12, 24 h after treatments. Moreover, effects of different doses of PGE2 application on the concentration of total PGF2α (PGF2α and its main metabolite 13,-14- dihdro-15-keto- prostaglandin F2α-PGFM) was determined. The time point of PGE2, hCG or saline administration was defined as hour “0” of the experiment. An intra–CL injection of PGE2 increased P4 and PGE2 concentrations between 3 h and 4 h or at 3 h and 12 h, respectively (P < 0.05). While intra–U administration of PGE2 elevated P4 concentrations between 8 and 24 h; PGE2 was up-regulated at 1 h and between 3 h and 4 h(P < 0.05). An intra–CL injection of hCG increased P4 concentrations at 1 h, 6 h and 12 h (P < 0.05), while its intra–U administration enhanced P4 and PGE2 concentrations between 1 h and 12 h or at 3 h and between 6 h and 10 h, respectively (P < 0.05). An application of PGE2, dependently on the dose, supports equine CL function, regardless of the application site, consequently leading to differences in both P4 and PGE2 concentrations in blood plasma.